The Culture of the WTO: Why it Needs to Change - Steger, Debra (Eurostudia)

(untitled) (Le Centre canadien d'études allemandes et européennes, 2007)
AbstractWTO works like any institution following a set of rules and regulations. The article traces this “culture” since its beginnings in the framework of GATT sixty years ago. Even though some of its elements like for example the Dispute settlement mechanism (DSM) are considerable achievements, the present deadlock of the Doha round reveals the need for reform. Various modifications are necessary like for example the abandon of the principle of unanimity in its decision-making process, an enlargement of its agenda from simple liberalization issues to real development politics and the regulation of financial markets and international investment.